Transformation of Libraries with AI –powered Knowledge Graphs (LIS TODAY, 2026)
Libraries cannot be exclusively associated with physical books or printed materials  anymore due to the emergence of the digital era. Libraries have, therefore, shifted to  carrying enormous volumes of digital materials such as e-books and research articles.  Considering further that the amount of data is increasing even faster and traditional  search engines are becoming ineffective, new systems of information organization must  be delivered. Knowledge graphs present such systems and assist in how information is  categorized and searched. Since different databases are closely linked and related concepts  are interlinked, knowledge graphs improve search results and offer access to relevant  information more efficiently. The purpose of this present study is to demonstrate the  transformation that takes place in librarians’ worldviews thanks to knowledge graphs.  It does so by reviewing their design, advantages, and possible use. Issues of knowledge  extraction, knowledge representation, and subsystem development in mass information  systems are considered, as well as perspectives on their evolution.
Keywords: Knowledge Graphs; knowledge graph techniques; Term extraction; Knowledge Representation; Information Services